Tương tác của kali tricloro(safrol) platinat (II) với amoniac, đimetylamin và đietylamin. - Chi, Nguyễn Thị Thanh; Đà, Trần Thị; Đình, Nguyễn Hữu (Vietnam Journal of Chemistry, 2012)
Interaction of potassium trichloro(safrole)platinate(II) with ammonia, dimethylamine and diethylamine obeys the trans effect rule and leads to formation of trans-[Pt(Saf)(ammine)Cl2], trans-[Pt(Saf)(dimethylamine)Cl2], trans-[Pt(Saf)(diethylamine)Cl2]. The structure of these complexes have been determinded by elemental analysis, molar conductivity, IR, Raman, electronic, 1H NMR and NOESY spectra.